Studies in Turkiye within the context of Gender: An Overview of Postgraduate Dissertations - Filiz Göktuna Yaylacı (Journal of Economy Culture and Society)
The gender issue is a relatively new topic in migration studies. However, with increasing awareness, it has gained growing popularity among research topics dealing with human mobility. As a research interest, it also naturally stands out in Turkiye, a destination country for large-scale immigration movements. Considering all this, one can see the importance and necessity of examining studies that address gender and migration in tandem. Such an academic endeavor could bring about key results in terms of identifying more and less focused themes by gender and migration studies, thus helping formulate functional recommendations for further research. The main purpose of this study is to evaluate the postgraduate dissertations directly focusing on gender in the context of migration in Turkiye. To this end, 57 postgraduate dissertations were examined by the years they were completed, the universities in which they were made, the gender of authors, the methods of the dissertations in general, and the sample or study groups. The findings evaluated were based on the relevant literature. The findings show that there is a growing interest in the migration issue as part of the academic studies in Turkiye. However, the studies in the context of gender and migration are still limited. There is very little research on this subject at the doctoral level. The findings highlight the need for the diversification and enrichment of gender and migration studies in certain aspects.